FLOWERING AND FRUITING STUDY OF Melaleuca cajuputi subsp. cajuputi Powell AT PALIYAN SEEDLING SEED ORCHARD, GUNUNGKIDUL, YOGYAKARTA - Liliana Baskorowati; R Umiyati; Noor Khomsah Kartikawati; Anto Rimbawanto; Mudji Susanto (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2008)
Observation on of flowering and fruiting phenology were undertaken at M. cajuputi subsp. Cajuputi seedling seed orchard Paliyan, Gunungkidul from February to October 2002. Seed viability was tested out at Forest Biotechnology and Tree Improvement Research Institute, Yogyakarta. The objectives of this study are: (1) to identify the flowering time, (2) to determine the time of buds development and (3) to observe the reproductive success and the number of germination seeds per capsule of open pollination seeds. The study showed that peak flowering of M. cajuputi subsp cajuputi at Paliyan seedling seed orchard occurred in March; several trees at this population also flowered during February to June. The buds initiation to capsules maturity took on average of 277 days. Three months after fertilisation, the capsules were ready to harvest. Mean number of reproductive success of open pollination seeds is 3.6%. The mean number of seed viability varied between provenance range from 6 to 32 seeds/capsule.